(untitled) (Research, Society and Development, 2023)
Congenital syphilis occurs by transmission of Treponema Pallidum through the placenta from the mother to her fetus. Despite being a preventable disease, congenital syphilis continues to increase in Paraná and Brazil. This is an exploratory and quantitative study that sought to find the number of cases of congenital syphilis in the state of Paraná/BR in the city of Cascavel in the years 2020 and 2021. 9,829 newborns in the municipality of Cascavel/PR were analyzed, of which among the births, 37 cases of congenital syphilis were notified through the notification form. From the data, it was verified that there is still an increase in the number of cases of congenital syphilis, which probably occur due to inaccuracies in prenatal care, both by the health group and the patients. Given these data, it is necessary to improve the quality of prenatal care and inform pregnant women about the risks of congenital syphilis.